Factors affecting health care services utilization among the senior citizens in the coastal barangays of Miagao, Iloilo. - Guieb, Jude Barnard T.; Pormon, Miah Maye M. (2011.)
This paper examined the factors affecting health care services utilization among the 173 senior citizens in the 22 coastal barangays of Miag-ao, Iloilo. Specifically the paper described the socio-demographic and economic profile, health profile, health care services sought and the corresponding cost involved, and determiend the significant factors affecting the utilization of professional health care services among senior citizens. Data were collected through personal interviews in November to December 2010. There were 142 study participants who reported experiencing illness during the last twelve months prior to interview. The majority (53.5 percent) opted for self treatment, traditional healing or did nothing. Those who sought professional care (46.4 perent) visited private clinics, the Rural Health Unit (RHU) and private hospitals. Two regression were done. The first regression showed three significant factors affecting health care utilization of senior citizens for the past 12 months: educational attainment ( 5 percent level of significance) and the presence of chronic disease and disability (10 percent). In the second regression, three factors were found to affect the health care utilization of senior citizens during their last reported illness: household income and educational attainment (5 percent lvel of significance), and monetary cost (10 percent level of significance ). The study recommends for the strict observance of the 20 percent discount on the prices of medicines of the senior citizens, information dissemination activities targeted to low income senior citizens and for a medical mission for them.
Research Paper (Undergraduate, Bachelor of Science in Economics) College of Arts and Sciences,University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Health Care Services -- Senior Citizens -- Miagao, Iloilo